IMPLEMENTASI PEMBELAJARAN TAHFIDZUL QUR`AN DENGAN METODE MURI-Q PADA SISWA DI SEKOLAH DASAR NEGERI 3 CERMO SAMBI BOYOLALI - Tugiman, T; Fatimah, Meti; Faiz, Rexsi Azmi; Listianto, Dwiyan; Kirstyaustin, Jhil Alesia (AL HAZIQ: Journal of Community Service, 2025)
This Community Service project aims to analyze the implementation of Tahfidzul Qur’an learning using the MURI-Q method among students at SD Negeri 3 Cermo, Sambi, Boyolali. The MURI-Q method is an innovative approach to Qur’an memorization that emphasizes repetition, understanding, and systematic motivation. The results of the study indicate that the application of the MURI-Q method at SD Negeri 3 Cermo has been effective, supported by educators, learning facilities, and active student participation. Supporting factors include the use of gradual memorization techniques, a continuous evaluation system, and motivation through rewards. However, the study also identified several challenges, such as the consistency level of students in memorizing and the limited time allocated in the school curriculum. Overall, the MURI-Q method has proven to significantly enhance students’ memorization abilities and foster their love for the Qur’an.